2017
DOI: 10.1186/s13104-017-2998-6
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected pulmonary tumor: metastasis from a benign uterine leiomyoma in a post-menopausal woman: a case report

Abstract: BackgroundThe occurrence of lung metastasis from benign uterine leiomyomas is rarely reported especially in post menopausal women. The pathogenesis of these metastatic benign tumors still remains a subject of various speculations.Case presentationA 57-year-old woman presented with a chronic cough and dyspnea. She had undergone 8 years previously, hysterectomy for benign leiomyomas. A chest computed tomography scan showed a 4 cm solitary nodular parenchymal tumor that increased in size after 12 months. The hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…Most cases of BML have occurred after a uterine leiomyoma surgery. Therefore, it was suggested that the smooth muscle cells may be hemodynamically or directly seeded due to tissue damage caused by the surgical procedure 1,3,4 . However, there were a few reports in which BML were found in women with no history of uterus surgeries, 5 and the surgical procedures were not always associated with the development of metastatic leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of BML have occurred after a uterine leiomyoma surgery. Therefore, it was suggested that the smooth muscle cells may be hemodynamically or directly seeded due to tissue damage caused by the surgical procedure 1,3,4 . However, there were a few reports in which BML were found in women with no history of uterus surgeries, 5 and the surgical procedures were not always associated with the development of metastatic leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that the smooth muscle cells may be hemodynamically or directly seeded due to tissue damage caused by the surgical procedure. 1,3,4 However, there were a few reports in which BML were found in women with no history of uterus surgeries, 5 and the surgical procedures were not always associated with the development of metastatic leiomyoma. It has been also proposed that the primary lesion of the uterus itself had the potential of an extremely low-grade leiomyosarcoma, 6 but it is very difficult to clearly histopathological classify benign and malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no guidelines for treatment of BML, given how rare the condition is, and most treatment is based on location and disease burden [2, 5]. BML are indolent in nature and treatment can involve targeted hormonal therapies and surgery [2].…”
Section: Discussionmentioning
confidence: 99%
“…At this point it was decided to proceed with right oophorectomy to decrease hormonal exposure. As BML are an indolent disease long term radiological surveillance is required with either CT or MRI to monitor for disease progression [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation